Origin of V-Cr-Ti-mineralization in thermally overprinted metal-rich black shales from the Tepla-Barrandian Unit (Bohemian Massif) and implications for metal remobilization during metamorphism - Veselovsky,F.; Pasava,J.; Pour,O.; Ackerman,L. (Journal of Geosciences, 2021)
We present a detailed study of geochemical composition and ore mineralogy of black shales from Chynin, Czech Republic, representing Ediacaran organic matter-rich sediments, which were subject to regional and contact metamorphism. They are part of the Blovice Accretionaly Complex (BAC) in the Tepla-Barrandian Unit (TBU) and are located close to the contact with the Central Bohemian Pluton (CBP). The black shales were encountered with metasilicites, metabasalts, and basic tuffitic rocks in the CHY-2 drill hole (250 m deep) and are regionally associated with hornfels bodies. The geochemistry of these shales indicates that they correspond to metal-rich black shales deposited under strongly reducing conditions (TOC/P molar > 100, high Mo and U values). On the other hand, the lack of a positive link between TOC and redox-sensitive metals (e.g., V, U, Cr, Ni, Mo) and their generally negative correlation with sulfur indicate important late-stage metal and sulfur remobilization. This is reflected in the mineralogical composition of the shales, which documents a thermal event in their history. Abundant framboidal pyrite (pyrite I) was recrystallized into coarse aggregates (pyrite II), locally accompanied by chalcopyrite, sphalerite, and rare molybdenite, pentlandite and breithauptite. Abundant pyrrhotite formed there due to selective desulfurization of pyrite I and II during the contact metamorphism. Locally, this process was also accompanied by the replacement of pyrrhotite by V-Cr-O (karelianite - V2O3 and eskolaite - Cr2O3, mostly with dominant karelianite end-member) and Ti-V-O (vanadium rutile, schreyerite - V2Ti3O9 and a phase with the theoretical composition V4Ti3O12, yet unknown to the mineralogical system). Vanadium-Cr-Ti elemental associations reported from different localities of Neoproterozoic metal-rich black shales, metal-rich black shales, and (meta)silicites in TBU indicate similar sources of these elements but different conditions of their accumulation.
Keywords: V-Cr-Ti oxides; metal-rich black shales; Neoproterozoic; contact metamorphism